1984
DOI: 10.1084/jem.159.3.704
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functional sites on a single Ia molecule defined using T cell clones and antibodies with chain-determined specificity.

Abstract: Monoclonal antibodies (mAb) were used to inhibit the proliferation of antigen-reactive (C57BL6/J X A/J)F1 restricted T cell clones. We have been able to subdivide these F1 restricted T cell clones into two groups: one of which recognizes the A alpha k A beta b molecule and the other group which recognizes the A alpha b A beta k molecule. Using clones with defined reactivities, we could assign the reactivities of monoclonals to the A alpha or A beta chains. By immunoprecipitation and two-dimensional analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 28 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…Finally, competitive binding assays with pairs of anti-Ia mAbs have revealed that the A and E complexes contain several partially or non-overlapping epitopes (11,12). Parallel Ab-blocking studies with these mAbs have shown that T cells, too, are capable of distinguishing several epitopes on an Ia molecule (8,9,13). In summary, it seems that the understanding of what a T cell "sees" on an Ia antigen has increased in parallel with our ability to precisely assign Ia determinants.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Finally, competitive binding assays with pairs of anti-Ia mAbs have revealed that the A and E complexes contain several partially or non-overlapping epitopes (11,12). Parallel Ab-blocking studies with these mAbs have shown that T cells, too, are capable of distinguishing several epitopes on an Ia molecule (8,9,13). In summary, it seems that the understanding of what a T cell "sees" on an Ia antigen has increased in parallel with our ability to precisely assign Ia determinants.…”
mentioning
confidence: 91%
“…More recently, however, the response to poly(Glu6WAlaIOTyrlO) has been studied for isolated T-cell clones and the results appear somewhat different (13 (8,9). An earlier report had placed a component of Ia.2 on Ap because of its ability to precipitate the isolated chain (7), but the significance of this contradiction is unclear since none of the mAbs could precipitate the isolated Aa chain and since the specificity assignment of the anti-Ia.2 used in these experiments is now doubtful (25 that Arg-57 and Glu-75 lie within T-cell restriction sites on the Aa chain.…”
mentioning
confidence: 99%
See 3 more Smart Citations